Mathematical Knowledge at Escola Normal Evangélica (Evangelical Normal School) in São Leopoldo - Circe Mary Silva da Silva (Universidade Federal do Rio Grande do Sul, 2021)
The methods of document analysis and oral history were used to identify the place of mathematical knowledge in the Escola Normal Evangélica from 1950 to 1962. The sources used in the research were reports, photographs, official correspondence, newspaper articles of the time, circulars, bulletins, school notebooks and interviews. We concluded that the mathematical knowledge taught in the normal course, in the analyzed period, was compatible with that of regional normal schools, involving the contents of arithmetic, algebra and geometry. Pedagogical transfers took place between Brazil and Germany and, in addition, there were appropriations of knowledge for teaching, as a result of the approximation with other normal schools in the Brazilian state of Rio Grande do Sul.